Trajectory of adaptations done by families of children and teenagers with low vision - Mayara Caroline Barbieri; Gabriela Van Der Zwaan Broekman; Amanda Aparecida Borges; Monika Wernet; Regina Aparecida Garcia de Lima; Giselle Dupas (Universidade Federal do Rio de Janeiro, 2019)
ABSTRACT Objective: to understand the experience of families of children and adolescents with visual impairment with an emphasis on the adaptations made in daily life. Method: qualitative, research, which used as a theoretical reference the Symbolic Interactionism and analysis of narrative as method. Data collection through a semi-structured interview, recorded with 18 families of children and adolescents with visual impairment, totaling 61 participants from two municipalities in the interior of the state of São Paulo. Results: the analysis of the narratives allowed the understanding of 2 themes: diagnosis: an unexpected and daily process in front of the knowledge of DV. Final considerations: the family makes its own movement of modifications that have been present throughout the trajectory traveled by the members, which are full of interactions and meanings. It is necessary to train health professionals so that they can support the families of children and adolescents with visual impairment with the necessary information and support.